Pengembangan Karir dan Motivasi Kerja terhadap Kinerja Pegawai Negeri Sipil (PNS) pada Kantor Balai Standardisasi dan Pelayanan Jasa Industri di Samarinda - Lina Dimayanti; Askiah Askiah; Sofia Ulfa Eka Hadiyanti (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
An organization's success is highly dependent on the quality of the performance of employees who carry out their duties and responsibilities. In achieving organizational goals effectively and efficiently, HR management strategies are needed, one of which is career development and work motivation on employee performance. This study aims to analyze the effect of career development and work motivation on the performance of civil servants (PNS) at the Samarinda Office of the Standardization and Industrial Services Center (BSPJI). The approach used is quantitative with the sampling technique is saturated sampling, data collection from questionnaires distributed to 30 respondents. Data analysis was carried out using instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis testing using the SPSS application. The results showed that career development had a positive and significant effect on the performance of civil servants (PNS) at the Office of the Industrial Services Standardization and Services Center in Samarinda. Likewise with work motivation which has a positive and significant effect on the performance of civil servants at the Office of the Industrial Services Standardization and Services Center in Samarinda.